Nova planerska kultura - iniciativa za varstvo okolja - Sitar, Metka (Urbani izziv, 1998)
The emphasis in the text is on questions concerning the future of spatial planning, whereby the most important ones are survival of humanity and the creation of healty and pleasant environments. They are followed by questions on dillemas of planning for the future and the introduction of new procedures and instruments into the planning practice.
Keywords: ecology; ekologija; environmental protection; naselja; prostorsko planiranje; spatial planning; urbanistično planiranje; varstvo okolja